Acute Effects of Static Stretching, Active Warm Up, or Passive Warm Up on Flexibility of the Plantar Flexor Muscles of Iranian Professional Female Taekwondo Athletes. Issue 3 (September 2013) - Nuri, Leila; Ghotbi, Nastaran; Faghihzadeh, Soghrat
Abstract Objectives: Muscle flexibility is an important component of injury prevention in athletes. Active warm-up, passive warm-up and static stretching are different methods for increasing flexibility. Little clinical evidence is available regarding which of these methods has a greater role in increasing flexibility. This study was performed to compare acute effects of the above methods on the flexibility of the plantar flexor muscles of professional female taekwondo athletes. Methods: Female professional taekwondo athletes were randomly classified into three intervention protocol groups [active warm-up, passive warm-up, or static stretching, respectively]. Passive and active range of motion [ROM] was measured using a universal goniometer before and immediately after performing each of the designated flexibility protocols. Results: Thirty female athletes participated, providing 10 subjects for each group. There were no differences in age or body mass index between groups. The static-stretching protocol significantly increased active [p = 0.001] and passive [p = 0.001] ROM. The active warm-up protocol did not change either the active or passive ROM [p > 0.05]. The passive warm up protocol increased only the active ROM [p = 0.04]. Post hoc testing showed a significant difference not only between static stretching and active warm-up groups [p = 0.000], but also between static stretching and passive warm-up groups [p = 0.000]. There was no significant difference between the passive and active warm-up groups [p > 0.05]. Conclusions: Static stretching only protocol increased flexibility more than active and passive warm-up only protocols.